The development of a method for determining the biological activity of erythropoietin preparations in vitro - N. A. Gavrilova; S. A. Cherepushkin; N. V. Rykalina; Yu. I. Obukhov (Биопрепараты: Профилактика, диагностика, лечение)
The method for the assessment of biological activity of erythropoietin preparations in vitro on TF-1 sensitive cells culture has been developed. The special characteristics of measurements and calculations of the biological activity of erythropoietin with different levels of glycosylation in vivo and in vitro. Linear response ranges for cell lines to erythropoietin and its hyperglycosylated analogue differ and make (0.39-0.56 ng/ml) and (3.1-12.5 ng/ml), respectively. The results have shown the possibility of using cellular test for comparing and assaying the activity of erythropoietin analogues in standard international units of biological activity (IU) set for erythropoietin.